Willingness to Contribute Time versus Willingness to Pay for the Management of Harmful Algal Blooms - Roland O. Ofori (Phycology, 2023)
The harmful impacts of the ongoing Sargassum invasions in the Atlantic Ocean include fish kills, skin and eye irritation, beach fouling, and declines in fisheries and tourism in West Africa and the Americas. This study was conducted to address important gaps in the non-market valuation literature and support the design of effective adaptation policies to reduce the harmful impacts of algal blooms. Contingent valuation survey data and linear mixed-effects regression models were utilized to estimate the drivers of willingness to pay (WTP) and willingness to contribute time (WTCT) for the management of invasive Sargassum seaweeds in Ghana. The study revealed that income, education, family size, years of residence, sex, attitudes, and political affiliation are significant drivers of WTP, while distance to the beach, occupation, house ownership, attitudes, and political affiliation are also significant predictors of WTCT. Hence, only attitudes about invasive seaweeds and political affiliation influence both WTP and WTCT. The findings suggest that for developing countries to generate enough funding and adequate economic support for coastal resource conservation, they should design local resource protection programs that give residents the option to contribute both time and money.